The Effectiveness of the Deradicalization Program in Preventing Terrorism in Indonesia: Challenges of Reintegration and Its Implications for National Security - Kamal; Purnawati, Andi; Lubis, Mukhlis (Faculty of Law, Universitas Pekalongan, 2024)
In recent years, deradicalization programs have gained increasing importance in Indonesia's efforts to combat terrorism and ensure national security. However, despite their implementation, the effectiveness of these programs, particularly in terms of social reintegration, remains a key challenge. This study aims to evaluate the effectiveness of Indonesia’s deradicalization program, focusing on both ideological change and social reintegration of former extremists. Using a qualitative approach, the research conducted in-depth interviews, participant observations, and document analysis involving former terrorists, BNPT officials, and religious leaders. The findings reveal that while ideological shifts were successfully achieved through religious and psychosocial approaches, challenges in social reintegration, such as societal stigma and lack of family support, continue to hinder long-term success. The research underscores the importance of a more comprehensive approach to deradicalization, emphasizing social reintegration strategies to ensure sustained national security. The study offers practical recommendations for policymakers to strengthen post-program support, including anti-stigma campaigns and community-based reintegration initiatives. These findings contribute to the broader discourse on counterterrorism and deradicalization strategies in Indonesia